Information System Design in Predicting Production Quantity with the Monte Carlo Method - Dinda Ridho Putri Gulo (Universitas Putra Indonesia YPTK Padang, 2022)
Flying Horse Coffee is one of the well-known brands of ground coffee in Padang. Each period this coffee company produces large quantities of coffee, so that the manufacture of coffee only refers to the maker. Therefore, it is important to plan on the amount of coffee production so that the Company does not experience large losses due to the remaining unsold coffee because it is not precise in determining the amount of production. The purpose of this study was to determine the amount of coffee production prediction accurately in preparing the required resources. This study uses Monte Carlo Logic in planning the amount of production. The Monte Carlo method is one of the sciences that developed the same way of thinking as humans and can analyze problems that contain elements of uncertainty. The data that is processed is data on demand, supply and production based on the results of per period reports. Results This study uses the Monte Carlo method to predict the amount of coffee production accurately, from testing 44 samples of test data. The Monte Carlo method can predict the amount of production so that it can be used as a recommendation for the Company in predicting the amount of coffee production optimally. And then the company can minimize losses caused by inappropriate production